Spatial dynamic simulation of beetles in biodiversity hotspots - He, Ping; Bai, Ming; Li, Lulu; Lu, Yuanyuan; Li, Jing; Yan, Zihan (Frontiers in Ecology and Evolution, 2024)
Coleoptera is the most species-rich order of animals with the widest distribution area; however, little is known about its global suitability distribution, and a substantial number of species are experiencing silent extinction. Most of Earth's biocommunities are concentrated in biodiversity hotspots, and these hotspots receive the largest investment of conservation funds. The survival of beetles is closely related to the richness of biodiversity, so habitat loss in hotspots results in a high extinction risk for beetles. We used the MaxEnt model to simulate the spatial suitable distribution in six